Mimotope mimicking epidermal growth factor receptor alleviates mononuclear cell infiltration in exocrine glands induced by muscarinic acetylcholine 3 receptor - Yang, Lin (Clinical immunology (Orlando, Fla.), 2016)
Copyright © 2016 Elsevier Inc. All rights reserved.